Environmentally friendly impregnation system for fiber surface treatment, preparation method thereof, and impregnation treatment method

By using a new environmentally friendly impregnation system between fiber and rubber, including hydroxyacrylic resin, amino resin and other components, the problem of insufficient adhesion performance between fiber and rubber and the use of toxic substances in the prior art is solved, and an efficient and environmentally friendly adhesion effect between fiber and rubber is achieved.

CN115748256BActive Publication Date: 2025-04-11BEIJING UNIV OF CHEM TECH
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202111107619.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-09-02
Filing Date
2021-09-22
Publication Date
2025-04-11
Estimated Expiration
2041-09-22

AI Technical Summary

Technical Problem

The adhesion between existing fibers and rubbers has not reached the RFL level, and the raw materials used are highly purchased, the process is complex, and there is a problem of using toxic substances resorcinol and formaldehyde.

Method used

A new environmentally friendly impregnation system is adopted, which includes hydroxyacrylic resin, amino resin, blocked isocyanate, accelerator and rubber latex. The adhesion between fiber and rubber is significantly improved by the treatment of single-bath or double-bath impregnation liquid.

Benefits of technology

It achieves excellent bonding effect between fiber and rubber matrix, can replace the traditional RFL glue-impregnation system, and avoids the use of toxic substances, which is simple in process and low in cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003272939440000021
    Figure BDA0003272939440000021
  • Figure BDA0003272939440000031
    Figure BDA0003272939440000031
  • Figure BDA0003272939440000032
    Figure BDA0003272939440000032
Patent Text Reader

Abstract

The present invention discloses an environmentally friendly impregnation system for fiber surface treatment, a preparation method thereof and an impregnation treatment method. The environmentally friendly impregnation system for fiber surface treatment of the present invention comprises hydroxy acrylic resin, amino resin, epoxy resin, blocked isocyanate, accelerator, rubber latex and deionized water. The present invention can select single-bath impregnation treatment or double-bath impregnation treatment according to different fiber types and uses. The present invention can effectively replace the use of toxic raw materials and intermediates in traditional RFL dipping systems, reduce harm to human body and environment, and achieve the bonding effect of RFL.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fiber dipping, and in particular relates to an environmentally friendly impregnation system for fiber surface treatment and a preparation method and an impregnation treatment method thereof, and is particularly suitable for rubber skeleton materials. Background Art

[0002] Fiber cords and tire cord fabrics are widely used as reinforcing materials for rubber in products such as tires, hoses, and conveyor belts. The interfacial adhesion between the fiber and the rubber matrix is ​​crucial to the reinforcing effect of the fiber. Since 1935, the resorcinol-formaldehyde-latex (RFL) impregnation method has become the most effective method to improve the adhesion between the fiber and rubber. However, both resorcinol and formaldehyde in the RFL system are toxic substances, which have serious toxic effects on the human body and the environment. Resorcinol is prone to itching when in contact with the skin, and is toxic to the liver and cardiovascular system. Formaldehyde is more harmful to human health and safety than resorcinol. As early as 2004, the International Agency for Research on Cancer (IARC) of the World Health Organization listed it as a carcinogen that can easily cause leukemia. Therefore, there is an urgent need to develop a new environmentally friendly fiber impregnation treatment system to replace the traditional RFL system.

[0003] Patents US20150314644A1 (WO2014091429A1), US2012041113A1 (WO2010125992A1), US5565507A (WO9600749A1), and CN105839413A disclose environmentally friendly dipping solutions based on epoxy resin. Among them, US2015314644A1 discloses a bonding formula composed of rubber latex, epoxy compounds, and polyamines with a molecular weight greater than 190 Daltons. The viscosity of these compositions between the fiber skeleton material and the rubber is close to that of the traditional RFL system. US2012041113A1 discloses a dipping solution composed of epoxy resin, amino curing agent, blocked isocyanate, and rubber latex, which is used to enhance the bonding performance between fiber fabrics and rubber. US5565507A discloses a dipping solution composed of an epoxy resin with a functionality of more than three and a latex containing a carboxyl group, an amino group or a pyridine group. CN105839413A discloses a dipping system composed of an epoxy resin, an amine curing agent and a latex, and its bonding effect is better than the RFL treatment level.

[0004] Patents CN112176729A (WO2021000918A1), US2005147817A1, and US2005255773A1 disclose environmentally friendly dipping solutions with maleic anhydride polymer as the main body. Among them, CN112176729A discloses a dipping system composed of maleic anhydride polymer, epoxy resin, blocked isocyanate, curing agent, rubber latex, and optional component filler. The fiber treated with this dipping system has excellent bonding properties and can achieve the bonding effect of RFL. US2005147817A1 discloses a dipping solution composed of semi-esterified maleic anhydride polybutadiene, carbon black, latex, etc., which can effectively improve the bonding between fiber and EPDM rubber. US2005255773A1 discloses a dipping solution composed of maleic anhydride polyolefin, maleimide resin, vinyl unsaturated carboxylic acid metal salt and latex, which is used to improve the bonding performance between fiber and rubber.

[0005] Patents US2015315410A1, US4472463A, and CN109097993A disclose environmentally friendly dipping solutions based on acrylic resin. Among them, US2015315410A1 discloses a dipping solution composed of carboxyl acrylic resin, epoxy resin, blocked isocyanate, and latex, and its bonding effect is slightly better than RFL. The dipping solution of US4472463A contains acrylic monomers and a small amount of styrene copolymers and latex, and its bonding effect is slightly better than the RFL dipping system. CN109097993A discloses a dipping system composed of self-crosslinking acrylic resin, blocked isocyanate, and rubber latex, which achieves good adhesion between the dipped fabric and rubber, reaching or exceeding the dipping effect of traditional RFL.

[0006] CN106120350A discloses an impregnation treatment system comprising tannic acid, polyamine, and latex. The bonding effect of polyester cord treated by this method is equivalent to that of RFL, and the bonding effect at high temperature is better than that of RFL. CN110284326A discloses an impregnation treatment system comprising special amino resin (mainly benzoxazine resin), blocked isocyanate, additives, and latex. The bonding effect of nylon fiber treated by this method can reach the level of RFL.

[0007] Although the prior art has made some improvements in improving the bonding performance between fiber and rubber, there are still some problems in the prior art, mainly including that the bonding strength of the impregnation system provided does not reach the RFL level; some raw materials used in the formula have strict requirements and high procurement costs; or there are problems with complex processes. Therefore, there is a need for a new environmentally friendly impregnation system for fiber surface treatment that can significantly improve the bonding performance between fiber and rubber, can replace the RFL dipping system currently used in industry, and can avoid the use of toxic substances such as resorcinol and formaldehyde. Summary of the invention

[0008] In a first aspect, the present invention provides an environmentally friendly impregnation system for fiber surface treatment, comprising the following components in parts by weight:

[0009]

[0010] Preferably, the environmentally friendly impregnation system for fiber surface treatment provided by the present invention comprises the following components in parts by weight:

[0011]

[0012] More preferably, the environmentally friendly impregnation system for fiber surface treatment provided by the present invention comprises the following components in parts by weight:

[0013]

[0014] According to some specific embodiments of the present invention, the environmentally friendly impregnation system for fiber surface treatment is a single-bath impregnation liquid, wherein, by weight, it comprises the following components: 100 parts of deionized water; 1-30 parts of hydroxyl acrylic resin; 0.1-10 parts of amino resin; 1-10 parts of blocked isocyanate; 0.1-5 parts of accelerator; 50-180 parts of rubber latex. Preferably, the single-bath impregnation liquid contains epoxy resin, wherein, by weight, the environmentally friendly impregnation system comprises the following components: 100 parts of deionized water; 1-15 parts of hydroxyl acrylic resin; 0.1-8 parts of amino resin; 1-10 parts of epoxy resin; 1-10 parts of blocked isocyanate; 0.1-4 parts of accelerator; 50-150 parts of rubber latex.

[0015] According to some specific embodiments of the present invention, the environmentally friendly impregnation system for fiber surface treatment includes a first-bath impregnation liquid and a second-bath impregnation liquid: 1) the first-bath impregnation liquid, by weight, contains 0.5-2.5 parts of epoxy resin, 3-10 parts of blocked isocyanate and 90-110 parts of deionized water; 2) the second-bath impregnation liquid, by weight, contains 5-15 parts of hydroxylated acrylic resin, 0.5-3 parts of amino resin, 1-5 parts of accelerator, and 1-2 parts of rubber. 80-200 parts of latex and 90-110 parts of deionized water; preferably, 1) the first-bath immersion liquid, by weight, contains the following components: 1-2 parts of epoxy resin, 5-8 parts of blocked isocyanate and 95-105 parts of deionized water; 2) the second-bath immersion liquid, by weight, contains the following components: 7-10 parts of hydroxy acrylic resin, 1-2.5 parts of amino resin, 1.5-3 parts of accelerator, 100-180 parts of rubber latex and 95-105 parts of deionized water.

[0016] According to some embodiments of the present invention, the hydroxyl content of the hydroxyl acrylic resin is 2.0-5.0 wt %.

[0017] According to some embodiments of the present invention, the molecular weight (number average) of the hydroxy acrylic resin is 8000-15000.

[0018] According to some embodiments of the present invention, the amino resin can be dissolved in water or latex emulsion, and is preferably selected from at least one of urea-formaldehyde resin, melamine-formaldehyde resin, polyamide polyamine epichlorohydrin, etherified urea-formaldehyde resin, etherified glycoluril resin, fully methylated melamine resin, polymerized partially methylated melamine resin or polymerized high-imino methylated melamine resin. Preferably, the molecular weight (number average) of the amino resin can be 100-800.

[0019] According to some embodiments of the present invention, the epoxy resins can be dissolved in water or latex emulsion, and are preferably selected from at least one of bisphenol A epoxy resin, epoxidized linear phenolic resin, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, 1,2-propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, glycerol glycidyl ether, trimethylolpropane glycidyl ether, tetraphenol ethane tetraglycidyl ether epoxy resin, sorbitol glycidyl ether, resorcinol diglycidyl ether type epoxy resin and bisresorcinol formal tetraglycidyl ether.

[0020] According to some embodiments of the present invention, the blocked isocyanate is composed of an isocyanate and a blocking agent, the isocyanate is selected from at least one of trimethyl-1,6-hexamethylene diisocyanate, tetramethylene diisocyanate, tetramethyl diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, isophorone diisocyanate and diphenylmethane diisocyanate; the blocking agent is selected from at least one of ε-caprolactam, butanone oxime and phenol.

[0021] According to some embodiments of the present invention, the accelerator is selected from at least one of amine-blocked dinonylnaphthalene disulfonic acid, amine-blocked dinonylnaphthalene sulfonic acid, amine-blocked dodecylbenzene sulfonic acid or amine-blocked p-toluene sulfonic acid.

[0022] According to some embodiments of the present invention, the solid content of the rubber latex is 20 to 60 wt %, and the rubber latex is selected from butyl pyrrolidone latex, examples of which include but are not limited to carboxylated butyl pyrrolidone latex; styrene butadiene latex, examples of which include but are not limited to carboxylated styrene butadiene latex; styrene butadiene pyrrolidone latex, chloroprene latex, nitrile latex, examples of which include but are not limited to at least one of carboxylated nitrile latex or natural latex.

[0023] In a second aspect, the present invention also provides a method for preparing an environmentally friendly impregnation system for fiber surface treatment, wherein the method comprises the following steps:

[0024] Single-bath dipping solution system: hydroxy acrylic resin, amino resin, optional epoxy resin and accelerator are sequentially added into deionized water and stirred, then blocked isocyanate is added and stirred, and finally rubber latex is added and stirred to obtain a single-bath dipping solution;

[0025] The dosage of each component is as follows, by weight: 100 parts of deionized water; 1-30 parts of hydroxy acrylic resin; 0.1-10 parts of amino resin; 1-10 parts of blocked isocyanate; 0.1-5 parts of accelerator; 50-180 parts of rubber latex; or

[0026] Double-bath dipping solution system: 1) adding epoxy resin to deionized water and stirring, then adding blocked isocyanate and stirring to obtain a uniform reaction solution to prepare a first-bath dipping solution; 2) adding hydroxy acrylic resin, amino resin and accelerator to deionized water in sequence and stirring to obtain a uniform dispersion, and finally adding rubber latex and continuing to stir to obtain a second-bath dipping solution;

[0027] The first-bath dipping solution comprises, by weight, 1-2 parts of epoxy resin, 5-8 parts of blocked isocyanate and 95-105 parts of deionized water; the second-bath dipping solution comprises, by weight, 7-10 parts of hydroxy acrylic resin, 1-2.5 parts of amino resin, 1.5-3 parts of accelerator, 100-180 parts of rubber latex and 95-105 parts of deionized water.

[0028] In a third aspect, the present invention also provides an impregnation treatment method for fiber surface treatment, characterized in that the method comprises the following steps:

[0029] (A) placing the fiber in a single bath dipping solution for dipping;

[0030] (B) drying and curing the impregnated fibers obtained in step (A).

[0031] The dosage of each component in the single-bath dipping solution is calculated by weight: 100 parts of deionized water; 1-30 parts of hydroxy acrylic resin; 0.1-10 parts of amino resin; 1-10 parts of blocked isocyanate; 0.1-5 parts of accelerator and 50-180 parts of rubber latex.

[0032] According to some embodiments of the present invention, in step (A), the immersion is carried out at a temperature of 15-40° C. and for a time of 1-5 min.

[0033] According to some embodiments of the present invention, in step (B), the drying is carried out at a temperature of 110-160° C. and a time of 1-10 min.

[0034] According to some embodiments of the present invention, in step (B), the curing is carried out at a temperature of 180-250° C. and a time of 1-10 min.

[0035] According to some embodiments of the present invention, in step (A), the pH of the dipping solution is adjusted to alkaline before dipping. In some embodiments, the pH of the dipping solution is adjusted to alkaline by using an alkaline solution such as potassium hydroxide solution or ammonia solution, preferably with a pH of 8.0-11.0.

[0036] In a fourth aspect, the present invention further provides an impregnation treatment method for fiber surface treatment, characterized in that the method comprises the following steps:

[0037] i) placing the fiber in a bath impregnation liquid for impregnation, wherein the amount of each component of the bath impregnation liquid is, by weight, 0.5-2.5 parts of epoxy resin, 3-10 parts of blocked isocyanate and 90-110 parts of deionized water;

[0038] ii) drying the fibers treated in step i) and then curing them;

[0039] iii) placing the fiber treated in step ii) in a second-bath impregnation solution for impregnation, wherein the second-bath impregnation solution comprises, by weight, 5-15 parts of hydroxy acrylic resin, 0.5-3 parts of amino resin, 1-5 parts of accelerator, 80-200 parts of rubber latex and 90-110 parts of deionized water;

[0040] iv) drying and curing the fibers treated in step iii).

[0041] According to some embodiments of the present invention, in step i), the immersion is carried out at a temperature of 15-40° C. and for a time of 1-5 min.

[0042] According to some embodiments of the present invention, in step ii), the drying is performed at a temperature of 110-160° C. for a time of 1-10 min.

[0043] According to some embodiments of the present invention, in step ii), the curing is carried out at a temperature of 180-250° C. and a time of 1-10 min.

[0044] According to some embodiments of the present invention, in step iii), the immersion is carried out at a temperature of 15-40° C. and for a time of 1-5 min.

[0045] According to some embodiments of the present invention, in step iv), the drying is performed at a temperature of 110-160° C. for a time of 1-10 min.

[0046] According to some embodiments of the present invention, in step iv), the curing is performed at a temperature of 180-260° C. and a time of 1-10 min.

[0047] According to some embodiments of the present invention, in step iii), the pH of the second-bath impregnation solution is adjusted to alkaline before impregnation. In some embodiments, the pH of the impregnation solution is adjusted to alkaline by using an alkaline solution such as sodium hydroxide solution or ammonia solution, preferably with a pH of 8.0-11.0.

[0048] According to the treatment method of the present invention, the deionized water, hydroxy acrylic resin, amino resin, epoxy resin, blocked isocyanate, accelerator and rubber latex are the same as those described above and are not described in detail herein.

[0049] According to some embodiments of the present invention, the fiber includes cotton fiber, rayon, polyamide fiber, polyester fiber, aramid fiber, ultra-high molecular weight polyethylene fiber, polyimide fiber, carbon fiber or mixed twisted cords of the above fibers.

[0050] According to some embodiments of the present invention, the fiber is in a form selected from monofilament, bundled filament, twisted cord, canvas, cord fabric or a combination thereof.

[0051] The present invention proposes a novel environmentally friendly impregnation system for fiber surface treatment. Single bath impregnation treatment or double bath impregnation treatment can be selected according to different fiber types and uses.

[0052] The fiber treated by the impregnation system of the present invention has an excellent bonding effect with the rubber matrix, and can achieve the purpose of replacing RFL. At the same time, the fiber treated by the environmentally friendly impregnation system has little strength loss, which will not affect its use.

[0053] The present invention uses a single-bath immersion treatment to coat the fiber surface with hydroxy acrylic resin-amino resin-rubber latex. On the one hand, the hydroxy acrylic resin and the amino resin can react to form a resin network structure, and the polar group can react with the fiber; on the other hand, the rubber latex particles in the network structure can participate in the co-vulcanization of the rubber matrix, so that the fiber skeleton material and the rubber have better adhesion. When the double-bath immersion treatment is used, the fiber surface can first be activated by epoxy resin and isocyanate in one bath, and then the hydroxy acrylic resin-amino resin-rubber latex is coated with the second bath immersion liquid, so that the above-mentioned physical and chemical effects are formed between the fiber and the rubber matrix, and the adhesion performance is improved.

[0054] Advantages and features of the present invention:

[0055] 1. The dipping solution of the present invention realizes the use of no resorcinol and no formaldehyde, greatly reducing the harm to the environment and human body, and the preparation process of the dipping solution and the fiber impregnation process are simple, the reaction time is short, and it is conducive to industrial production.

[0056] 2. The raw materials used in the present invention are all industrial products with wide sources, low prices, and are all water-soluble.

[0057] 3. The viscosity of the impregnation liquid will not increase significantly when left at room temperature for a long time, which is conducive to the long-term storage and transportation of the impregnation liquid during the production process of fiber skeleton material impregnation. DETAILED DESCRIPTION

[0058] The raw materials used in the following examples and comparative examples are all commercially available, among which:

[0059] Hydroxylated acrylic resin: purchased from Guangzhou Dolphin New Materials Co., Ltd., with a number average molecular weight of about 10,000 and a hydroxyl content of 3.2 wt%.

[0060] Amino resin: purchased from Allnex Resins (China) Co., Ltd., with a number average molecular weight of about 600 and a solid content of 80 wt%. Sorbitol glycidyl ether: CAS 68412-01-1, purchased from Nan Ya Epoxy Resin Co., Ltd.

[0061] ε-caprolactam-terminated diphenylmethane diisocyanate: CAS 5101-68-8, brand CBI 50, purchased from Changzhou Keying Chemical Co., Ltd., solid content 50 wt%, particle size 1.5 μm.

[0062] Styrene-butadiene-vinyl pyridine latex (VP latex): brand VP-15, purchased from Jiangsu Yatai Chemical Co., Ltd., solid content 40wt%.

[0063] Resorcinol: CAS 108-46-3, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., purity ≥99wt%.

[0064] Formaldehyde: CAS 50-00-0, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., purity 37 wt%.

[0065] The preparation method of the H extraction force test strips in the following examples and comparative examples is as follows:

[0066] According to the standard GB / T2942-2009, the standard rubber (the standard rubber formula adopts GB / T9101-2017) is completely coated on the dipped cord, and then placed on a flat vulcanizer for vulcanization. The vulcanization temperature is 136°C, the vulcanization time is 50 minutes, and the vulcanization pressure is 15MPa.

[0067] The preparation method of the peeling force test strips in the following examples and comparative examples is as follows:

[0068] Refer to the peeling method of Shenma Industrial Co., Ltd. to determine the adhesion standard of nylon 66 dipped single cord. The rubber compound formula used for vulcanization is the same as that for H pull-out force test. The vulcanization temperature is 160℃, the vulcanization time is 20min, and the vulcanization pressure is 2.354Mpa.

[0069] The preparation method of the cord breaking strength test specimens in the following examples and comparative examples is as follows:

[0070] The standard GB / T32108-2015 is adopted, and the cord strength is tested by a tensile tester after the dipped cord is tested. The cord length in the test area is 250mm, and the tensile speed is 300mm / min.

[0071] In the following examples and comparative examples, the cord breaking strength test is tested according to GB / T32108-2015; the H extraction force is tested according to GB / T2942-2009; and the peeling force test method is as follows:

[0072] Vulcanization mold size: membrane cavity depth 2mm, length 250mm, width 170mm, each specimen width 20mm, interval between specimens 6mm, 10mm reserved on each side of the mold, the thickness of the cover plate and the mold bottom plate shall not be less than 10mm.

[0073] The rubber compound formula used for vulcanization is the same as that for the H pull-out force test.

[0074] Vulcanization process: 160℃×20min, pressure 2.354Mpa.

[0075] Vulcanization process: 1) After preheating the mold at 136℃ for 15-20 minutes, install a single cord into the groove to make the cord vertically tense; 2) Put a 20mm long, 160mm wide, 0.5mm thick film near the frame at the lower end of the mold and attach a cellophane slightly larger than the film on it; 3) Put a 240mm long, 160mm wide, 1.7mm thick film on the cellophane, and attach a lining cloth of the same size on it. Vulcanization is carried out after the mold is pressed and closed. Cool for at least 2 hours after vulcanization, and then trim the sample to test the peeling force (each sample contains 5 cords).

[0076] Test process: The part separated by the cellophane is clamped into the upper and lower clamps of the tensile machine at an angle of 180° for tensile peeling. The speed of the tensile machine is set to 300mm / min, and the peeling length is (150±10)mm. The average adhesion (N) is read according to the peeling curve, and the peeling force of a single cord is calculated.

[0077] Example 1

[0078] An environmentally friendly fiber surface impregnation treatment system, the single-bath method formula ratio is calculated by weight as follows:

[0079]

[0080] Preparation method of dipping solution: add hydroxy acrylic resin, amino resin and accelerator in the formula into deionized water in turn, and stir the solution vigorously for 3 hours with an electric stirrer; then, add blocked isocyanate and stir for 1 hour, and finally add rubber latex to the solution and keep stirring vigorously for 2 hours to obtain a single-bath dipping solution.

[0081] Dipping treatment method: Dip the fiber cord in the dipping liquid for 1 minute at room temperature, and then dry and cure in an oven. The drying temperature is 150°C, the drying time is 2 minutes, the curing temperature is 220°C, and the curing time is 2 minutes.

[0082] Example 2

[0083] An environmentally friendly fiber surface impregnation treatment system, the single-bath method formula ratio is calculated by weight as follows:

[0084]

[0085] Preparation method of dipping solution: add hydroxy acrylic resin, amino resin and accelerator in the formula into deionized water in turn, and stir the solution vigorously for 2 hours with an electric stirrer; then, add blocked isocyanate and stir for 30 minutes, and finally add rubber latex to the solution and keep stirring vigorously for 1 hour to obtain a single-bath dipping solution.

[0086] Dipping treatment method: Dip the fiber cord in the dipping liquid for 1.5 minutes at room temperature, and then dry and cure in an oven. The drying temperature is 150°C, the drying time is 3 minutes, the curing temperature is 210°C, and the curing time is 3 minutes.

[0087] Example 3

[0088] An environmentally friendly fiber surface impregnation treatment system, the single-bath method formula ratio is calculated by weight as follows:

[0089]

[0090] Preparation method of dipping solution: add hydroxy acrylic resin, amino resin and accelerator in the formula into deionized water in turn, and stir the solution vigorously for 1.5 hours with an electric stirrer; then, add blocked isocyanate and stir for 30 minutes, and finally add rubber latex to the solution and keep stirring vigorously for 1.5 hours to obtain a single-bath dipping solution.

[0091] Dipping treatment method: Dip the fiber cord in the dipping liquid for 1 minute at room temperature, and then dry and cure in an oven. The drying temperature is 150°C, the drying time is 1.5 minutes, the curing temperature is 225°C, and the curing time is 1.5 minutes.

[0092] Example 4

[0093] An environmentally friendly fiber surface impregnation treatment system, the single-bath method formula ratio is calculated by weight as follows:

[0094]

[0095]

[0096] Preparation method of dipping solution: add the epoxy resin described in the formula into deionized water and stir for 1 hour to obtain a uniform dispersion; then add hydroxyl acrylic resin, amino resin and blocked isocyanate in sequence and stir for 2 hours; then add accelerator and stir for 1 hour, and finally add rubber latex and continue stirring for 2 hours to obtain a single-bath dipping solution.

[0097] Dipping treatment method: Dip the fiber cord in the dipping liquid for 1 minute at room temperature, and then dry and cure in an oven. The drying temperature is 160°C, the drying time is 2 minutes, and the curing temperature is 210°C, and the curing time is 2 minutes.

[0098] Example 5

[0099] An environmentally friendly fiber surface impregnation treatment system, the single-bath method formula ratio is calculated by weight as follows:

[0100]

[0101] Preparation method of dipping solution: add the epoxy resin described in the formula into deionized water and stir for 1.5 hours to obtain a uniform dispersion; then add hydroxyl acrylic resin, amino resin and blocked isocyanate in sequence and stir for 1.5 hours; then add accelerator and stir for 1.5 hours, and finally add rubber latex and continue stirring for 2 hours to obtain a single-bath dipping solution.

[0102] Dipping treatment method: Dip the fiber cord in the dipping liquid for 1.5 minutes at room temperature, and then dry and cure in an oven. The drying temperature is 150°C, the drying time is 2 minutes, the curing temperature is 225°C, and the curing time is 2 minutes.

[0103] Example 6

[0104] An environmentally friendly fiber surface impregnation treatment system, the single-bath method formula ratio is calculated by weight as follows:

[0105]

[0106] Preparation method of dipping solution: add the epoxy resin described in the formula into deionized water and stir for 1.5 hours to obtain a uniform dispersion; then add hydroxyl acrylic resin, amino resin and blocked isocyanate in sequence and stir for 2 hours; then add accelerator and stir for 1.5 hours, and finally add rubber latex and continue stirring for 2 hours to obtain a single-bath dipping solution.

[0107] Dipping treatment method: Dip the fiber cord in the dipping liquid for 2 minutes at room temperature, and then dry and cure in an oven. The drying temperature is 160°C, the drying time is 1.5 minutes, the curing temperature is 220°C, and the curing time is 1.5 minutes.

[0108] Comparative Example 1

[0109] Comparative Example 1 is a traditional RFL dipping process, and the RFL formula is as follows:

[0110]

[0111]

[0112] Preparation of RFL: First, add sodium hydroxide into deionized water according to the above formula, stir for 10 minutes, then add resorcinol and stir for 10 minutes, then add formaldehyde aqueous solution and stir for 6 hours at room temperature to obtain a uniform reaction liquid; finally, add butylpyrrolidone latex and stir for 2 hours at room temperature, during which time add ammonia water to finally obtain RFL dipping solution.

[0113] RFL impregnation treatment method: The fiber cord is immersed in the impregnation liquid for 1 minute at room temperature, and then dried and cured in an oven. The drying temperature is 150°C, the drying time is 3 minutes, the curing temperature is 220°C, and the curing time is 3 minutes.

[0114] Application Examples 1 to 6 and Application Comparative Example 1 adopt a single bath method to treat different fiber cords. The cords used in Application Examples 1-1, 2-1, 3-1, 4-1, 5-1, 6-1 and Application Comparative Example 1-1 are nylon 6 cords (1170 dtex / 2); the cords used in Application Examples 1-2, 2-2, 3-2, 4-2, 5-2, 6-2 and Application Comparative Example 1-2 are nylon 66 cords (1400 dtex / 2).

[0115] The different fiber cords after the immersion treatment of Examples 1 to 6 and Comparative Example 1 were used to prepare test samples according to the above method, and H extraction test, peeling test and cord strength test were carried out. The test results are shown in Table 1.

[0116] Table 1 Data of fiber cord treated by single bath method

[0117]

[0118] From the results in Table 1, it can be seen that the H extraction performance and peeling force of the two fiber cords of Examples 1 to 3 are basically equivalent to the RFL treatment effect of the comparative example. On this basis, by adding epoxy resin, that is, the treatment effect of Examples 4 to 6 is compared with the RFL bonding performance of the comparative example, the bonding effect of the two fiber cords is further improved. And from the test results of the cord strength, the strength loss of the fiber treated by this method is not large, and will not affect its use. In summary, the fiber and the rubber matrix have excellent bonding effect after being treated with a single bath of the new environmentally friendly impregnation system, which can effectively replace the RFL impregnation system.

[0119] Example 7

[0120] An environmentally friendly fiber surface impregnation treatment system, the double-bath method formula ratio is calculated by weight as follows:

[0121]

[0122] Preparation of dipping solution: In the first step, the water-soluble epoxy resin described in the formula is added to deionized water and stirred for 15 minutes, and then the blocked isocyanate is added and stirred for 1 hour to obtain a uniform reaction solution to prepare a one-bath dipping solution; in the second step, the hydroxy acrylic resin described in the formula is added to deionized water and stirred for 1.5 hours to obtain a uniform dispersion; then the amino resin and the accelerator are added and stirred for 30 minutes, and finally the rubber latex is added and stirred for 1.5 hours to obtain a two-bath dipping solution.

[0123] Dipping treatment: first place the fiber cord in a first-bath impregnation liquid, impregnate at room temperature for 2 minutes, dry at 130°C for 1 minute, and cure at 210°C for 2 minutes; then place the fiber in a second-bath impregnation liquid, impregnate at room temperature for 2 minutes, dry at 130°C for 2 minutes, and finally cure at 210°C for 2 minutes to allow the impregnation liquid to adhere to the fiber surface.

[0124] Example 8

[0125] An environmentally friendly fiber surface impregnation treatment system, the double-bath method formula ratio is calculated by weight as follows:

[0126]

[0127]

[0128] Preparation of dipping solution: In the first step, the water-soluble epoxy resin described in the formula is added to deionized water and stirred for 1 hour, and then the blocked isocyanate is added and stirred for 30 minutes to obtain a uniform reaction solution to prepare a one-bath dipping solution; in the second step, the hydroxy acrylic resin described in the formula is added to deionized water and stirred for 2 hours to obtain a uniform dispersion; then the amino resin and the accelerator are added and stirred for 1 hour, and finally the rubber latex is added and stirred for 1.5 hours to obtain a two-bath dipping solution.

[0129] Dipping treatment: The fiber cord is first placed in a first-bath impregnation liquid, immersed at room temperature for 1 minute, dried at 130°C for 1.5 minutes, and cured at 210°C for 2 minutes; then the fiber is placed in a second-bath impregnation liquid, immersed at room temperature for 1 minute, dried at 160°C for 1.5 minutes, and finally cured at 210°C for 2 minutes, so that the impregnation liquid adheres to the fiber surface.

[0130] Comparative Example 2

[0131] Comparative Example 2 is a traditional RFL two-bath process, and the formula of the traditional RFL two-bath process is as follows:

[0132]

[0133] Preparation of dipping solution: first, add the water-soluble epoxy resin described in the formula into deionized water and stir for 15 minutes, then add blocked isocyanate and stir for 1 hour to obtain a one-bath dipping solution; then, according to the above formula, add sodium hydroxide into deionized water and stir for 10 minutes, then add resorcinol and stir for 10 minutes, finally add formaldehyde aqueous solution and stir at room temperature for 6 hours to obtain a uniform reaction solution, finally add butylpyrrolidone latex and stir at room temperature for 2 hours, during which time add ammonia water to finally obtain RFL dipping solution.

[0134] Dipping treatment: The fiber cord is first placed in a first-bath impregnation liquid, immersed at room temperature for 1 minute, dried at 130°C for 3 minutes, and cured at 220°C for 3 minutes; then the fiber is placed in a second-bath impregnation liquid, immersed at room temperature for 2 minutes, dried at 130°C for 3 minutes, and finally cured at 220°C for 3 minutes, so that the impregnation liquid adheres to the fiber surface.

[0135] Application Examples 7 to 8 and Application Comparative Example 2 use a double-bath method to treat different fiber cords. The cords treated in Application Examples 7-1, 8-1 and Application Comparative Example 2-1 are nylon 66 cords (1400 dtex / 2), the cords treated in Application Examples 7-2, 8-2 and Application Comparative Example 2-2 are aramid cords (1670 dtex / 2), the cords treated in Application Examples 7-3, 8-3 and Application Comparative Example 2-3 are polyester cords (1440 dtex / 2), and the cords treated in Application Examples 7-4, 8-4 and Application Comparative Example 2-4 are aramid / nylon 66 multi-twisted cords (A1670 dtex / 2+N2100 dtex / 1).

[0136] The different fiber cords after the immersion treatment of Examples 7 to 8 and Comparative Example 2 were used to prepare test samples according to the method described above, and H extraction test, peeling test and cord strength test were carried out. The test results are shown in Table 2.

[0137] Table 2 Data of fiber cord treated by double bath method

[0138]

[0139]

[0140] It can be seen from the results in Table 2 that the H extraction force and peeling force of different fiber cords in Examples 7 to 8 exceed the bonding effect of RFL in the comparative example. In particular, when the nylon 66 cord (1400dtex / 2) is treated with a two-bath method in Examples 7-1 and 7-2, the bonding effect after the impregnation treatment is better than that of the single-bath treatment. And from the test results of the cord strength, the strength loss of the fiber after the two-bath treatment is not large, and will not affect its use. In summary, the fiber after the two-bath treatment of the new environmentally friendly impregnation system has an excellent bonding effect with the rubber matrix, which can effectively replace the RFL impregnation system.

[0141] The embodiments described above are only preferred embodiments of the present invention and are not other forms of limitation to the present invention. Any modifications, equivalent changes and improvements made to the above embodiments without departing from the technical essence of the claims of the present invention shall still fall within the scope of protection of the claims of the present invention.

Claims

1. An environmentally friendly impregnation system for fiber surface treatment, comprising the following components in parts by weight: 100 parts of deionized water; 1-30 parts of hydroxy acrylic resin; Amino resin 0.1-10 parts; 1-10 parts of blocked isocyanate; Accelerator 0.1-5 parts; 50-180 parts of rubber latex.

2. The environmentally friendly impregnation system according to claim 1, characterized in that: The weight parts of each component are as follows: 100 parts of deionized water; 1-15 parts of hydroxy acrylic resin; Amino resin 0.1-8 parts; Epoxy resin 1-10 parts; 1-10 parts of blocked isocyanate; Accelerator 0.1-4 parts; 50-150 parts of rubber latex.

3. The environmentally friendly impregnation system according to claim 1, characterized in that: The environmentally friendly impregnation system for fiber surface treatment is a single-bath impregnation liquid, which comprises the following components by weight: 100 parts of deionized water; 1-30 parts of hydroxyl acrylic resin; 0.1-10 parts of amino resin; 1-10 parts of blocked isocyanate; 0.1-5 parts of accelerator; and 50-180 parts of rubber latex.

4. The environmentally friendly impregnation system according to claim 2, characterized in that: The environmentally friendly impregnation system for fiber surface treatment is a single-bath impregnation liquid, which contains epoxy resin. The environmentally friendly impregnation system contains the following components by weight: 100 parts of deionized water; 1-15 parts of hydroxyl acrylic resin; 0.1-8 parts of amino resin; 1-10 parts of epoxy resin; 1-10 parts of blocked isocyanate; 0.1-4 parts of accelerator; and 50-150 parts of rubber latex.

5. The environmentally friendly impregnation system according to claim 1 or 2, characterized in that: The hydroxyl content of the hydroxy acrylic resin is 2.0-5.0 wt % and the number average molecular weight is 8000-15000.

6. The environmentally friendly impregnation system according to claim 1 or 2, characterized in that: The amino resin is selected from at least one of urea-formaldehyde resin, melamine-formaldehyde resin, polyamide polyamine epichlorohydrin, etherified urea-formaldehyde resin, etherified glycoluril resin, fully methylated melamine resin, polymerized partially methylated melamine resin or polymerized high-imino methylated melamine resin.

7. The environmentally friendly impregnation system according to claim 2, characterized in that: The epoxy resin is selected from at least one of bisphenol A epoxy resin, epoxidized linear phenolic resin, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, 1,2-propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, diglycidyl ether, glycerol glycidyl ether, trimethylolpropane glycidyl ether, tetraphenol ethane tetraglycidyl ether epoxy resin, resorcinol diglycidyl ether type epoxy resin or bisresorcinol formal tetraglycidyl ether.

8. The environmentally friendly impregnation system according to claim 1 or 2, characterized in that: The blocked isocyanate is composed of an isocyanate and a blocking agent, wherein the isocyanate is selected from at least one of trimethyl-1,6-hexamethylene diisocyanate, tetramethylene diisocyanate, tetramethyl diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, isophorone diisocyanate and diphenylmethane diisocyanate; and the blocking agent is selected from at least one of ε-caprolactam, butanone oxime and phenol.

9. The environmentally friendly impregnation system according to claim 1 or 2, characterized in that: The accelerator is selected from at least one of amine-blocked dinonylnaphthalene disulfonic acid, amine-blocked dinonylnaphthalene sulfonic acid, amine-blocked dodecylbenzene sulfonic acid or amine-blocked p-toluene sulfonic acid.

10. The environmentally friendly impregnation system according to claim 1 or 2, characterized in that: The solid content of the rubber latex is 20-60wt%, and the rubber latex is selected from at least one of butyl pyrrolidone latex, styrene butadiene latex, styrene butadiene pyrrolidone latex, chloroprene latex, nitrile latex or natural latex.

11. A method for impregnation treatment of fiber surface treatment, characterized in that The method comprises the following steps: (A) placing the fiber in a single bath dipping solution for dipping; (B) drying and curing the impregnated fibers obtained in step (A); The dosage of each component in the single-bath dipping solution is calculated by weight: 100 parts of deionized water; 1-30 parts of hydroxy acrylic resin; 0.1-10 parts of amino resin; 1-10 parts of blocked isocyanate; 0.1-5 parts of accelerator and 50-180 parts of rubber latex.

12. A method for impregnation treatment of fiber surface treatment, characterized in that The method comprises the following steps: i) placing the fiber in a bath impregnation liquid for impregnation, wherein the amount of each component of the bath impregnation liquid is, by weight, 0.5-2.5 parts of epoxy resin, 3-10 parts of blocked isocyanate and 90-110 parts of deionized water; ii) drying the fibers treated in step i) and then curing them; iii) placing the fiber treated in step ii) in a second-bath impregnation solution for impregnation, wherein the second-bath impregnation solution comprises, by weight, 5-15 parts of hydroxy acrylic resin, 0.5-3 parts of amino resin, 1-5 parts of accelerator, 80-200 parts of rubber latex and 90-110 parts of deionized water; iv) drying and curing the fibers treated in step iii).

Citation Information

Patent Citations

  • Fiber fabric gum dipping liquid, and preparation method and application thereof

    CN105839413A

  • Formula of canvas gum dipping solution and canvas gum dipping preparation method

    CN106120350A

  • Dipping solution for fiber framework material

    CN109097993A

  • Nanometer reinforced environment-friendly impregnation system for fiber surface treatment, preparation method and impregnation method

    CN112176729A

  • Adhesive composition for adhering textiles to EPDM rubber

    US20050147817A1